Study of Surgical Maneuvers in Patients with Dizziness - Nasretdinova M. T.; Normurodov N. A.; Yusubov Sh. O. (Journal of Science in Medicine and Life, 2025)
Vestibular rehabilitation is a simple and effective method of treatment of patients with diseases of peripheral and central parts of vestibular analyzer. The diagnosis of vestibular disorders, estimation of severance and dynamics of patient’s state is conducted with use of clinical tests with high level of significance. Among such tests there are investigation of spontaneous and end-position nistagmus, Halmagy test, test “to stand up and go for time”, test “on one leg equilibration” and so on. Vestibular gymnastic is composed of exercises for visual stabilization and balance training. The results of observation research the purpose of which was to estimate the optimal duration of vestibular rehabilitation in patients with unilateral no progressive peripheral vestibular disorder are presented. The optimal duration of treatment was established to be as little as two months.